Penetapan Harta Asas Pembayaran Diat dalam Konteks Malaysia - Lukman Abdul Mutalib; Wan Abdul Fattah Wan Ismail; Ahmad Syukran Baharuddin; Mohd Radzniwan A Rashid; Naji Arafat Haji Mahat; Muhamad Darwisy Mohd Razali (Penerbit KUIS, 2024)
Indexed by MyCite